ISOLASI FITOSTEROL DARI BAWANG MERAH (Allium cepa L.) - Ahmad Musonnifin Aziz; Farikha Alfi Syahriyah; Ahmad Ihya’ Ulumuddin; Qurrota A’yuni (2477 - 6165, 2019)
Shallot is one of the kitchen spices that is often used by the community. Shallot contains several useful compounds and one of them is phytosterol. Along with the development of science and technology, phytosterol can be used to reduce blood cholesterol levels and prevent heart disease, so it is very beneficial for human health. In this study, phytosterol compounds were identified and isolated. The dried onion was then pureed and sifted to 100 mesh. The sieved powder was then extracted by reflux extraction method within 6 hours. The results of the extract were then isolated by column chromatography and identified by Thin Layer Chromatography (TLC). The TLC test used -sitosterol as a standard and anisaldehyde reagent as a stain appearance. The TLC plate which had stained appearance was then analyzed using the TLC Scanner method. The results of the TLC test showed that the extract of positive red onion was purple and contained fitosterol. The results of the TLC Scanner also show that the peak and spectrum of the samples were the same as the standard -sitosterol and positively contained fitosterol.